PERAN GANDA IBU SEBAGAI ORANG TUA TUNGGAL (SINGLE PARENTS) DALAM MENDIDIK KARAKTER ANAK-ANAKNYA - Candrawati, A A Ketut Sri (Universitas Tabanan, 2023)
This research aims to find out how the multiple roles and what efforts single parents make in educating the character of their children. Researchers see the role of a mother in educating, raising, and giving affection to her children, as well as being a breadwinner. This type of research is qualitative descriptive research, to obtain complete data regarding the dual roles of mothers who are single parents. Respondents in this study consisted of 2 people. First respondent is a 48 years old woman who works outside the home, the second respondent is a 40 years old woman who opens a business at her home. Data collection methods used in this research are interviews and observation. The results of the study show that due to social change factors where the mother is required to carry out the dual role of taking care of the household alone without the help of a husband or father of her children, as well as being a breadwinner for the needs of daily life. The conclusion of this research is that the informant, who is a single mother who works for a living outside the home, finds it difficult to manage her time in taking care of and raising her children. The advice from this study is that as a mother, you should give enough time to your children, pay attention, love, pay attention to their education so that their needs and rights as children can be fulfilled properly. As a single mother who does not have a companion in taking care of her children, it is better to learn how to manage spending from income so that it is used for more important needs.